2022
DOI: 10.1007/s10620-022-07770-8
|View full text |Cite
|
Sign up to set email alerts
|

Ustekinumab and Vedolizumab Are Equally Safe and Effective in Elderly Crohn’s Disease Patients

Abstract: Background Anti-tumour necrosis factor (anti-TNF) agents are associated with increased infection risk among elderly inflammatory bowel disease (IBD) patients, and thus, alternative biologics may be preferable. However, little comparative data exist on the safety and efficacy of vedolizumab and ustekinumab in elderly IBD patients. Aims To compare the safety and effectiveness of ustekinumab and vedolizumab in elderly Crohn’s disease patients. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In a propensity score-matched analysis, a similar effectiveness of USTE versus VEDO was reported in older CD patients with a comparable CCI score [ 47 ]. Finally, the largest elderly CD cohort with a prolonged follow-up came from the ENEIDA registry and compared elderly with matched younger patients according to prior anti-TNF treatment and smoking habits.…”
Section: Ustekinumabmentioning
confidence: 70%
See 2 more Smart Citations
“…In a propensity score-matched analysis, a similar effectiveness of USTE versus VEDO was reported in older CD patients with a comparable CCI score [ 47 ]. Finally, the largest elderly CD cohort with a prolonged follow-up came from the ENEIDA registry and compared elderly with matched younger patients according to prior anti-TNF treatment and smoking habits.…”
Section: Ustekinumabmentioning
confidence: 70%
“…Safety: Generally, the safety profile of USTE seems good and, in the smaller studies, serious infections were associated with concurrent steroid use but not with CCI [ 46 ]. In the aforementioned comparison study with USTE/VEDO, a similar rate of infections was reported for the two study drugs, and concomitant steroids were present in 20–25% of patients [ 47 ]. In this study, only on univariate analysis was CCI associated with serious infections.…”
Section: Ustekinumabmentioning
confidence: 73%
See 1 more Smart Citation
“…Among the 63 publications, 10‐72 58 were journal articles and 5 were international conference abstracts. Two conference abstracts 71,72 were replaced by subsequent published articles found in our search.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported comparable safety and effectiveness between vedolizumab and ustekinumab in an elderly cohort. [ 19 ] Some of the discrepant findings could be related to population differences across the studies. In particular, frailty has recently emerged as a significant predictor of adverse outcomes in IBD patients.…”
mentioning
confidence: 99%